Streetkids united - Pritchard, Tim (Documentary filmmaker); Film & Music Entertainment Ltd.; FeelSales (Firm) ([London. England ] : Film & Music Entertainment Production, 2010)
A group of homeless children in Durban are chosen to represent South Africa in the first ever Street Child World Cup. For them, football might be a way to a brighter future. To much of the outside world they are a nuisance, best hidden or ignored, but they aspire to much more. They want to be a team. --
Originally released as a motion picture in 2011.
Featured the Umthombo Young Stars.
Cinematographers, Ad Ahmed, Tim Pritchard ; editor, Anna Ksiȩzopolska ; music, Crispin Taylor.
Mostly in English; with English subtitles for non-English dialogs.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 14, 2020)
Keywords: Soccer -- South Africa -- Durban; Documentary films; Sports films; Nonfiction films; Internet videos; Streaming video